Analysis of Local History Material in the Independent Curriculum Class X History Book - Musthafa, Nurul Qhatami; Putra, Trio Nurul Fajri; Yulifar, Leli (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This research aims to find out how the use of textbooks in learning history and knowing the local history material in history textbooks. The method used in this research is a qualitative method with a library research approach. The sources used in this research come from primary sources, namely two Class X History Textbooks published by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia in 2021, as well as books, articles, and official websites. Based on the results of the research, it was found that the Merdeka Curriculum class X high school textbook contains local history material, which contains the simplest things, such as students being directed to analyse historical phenomena in everyday life from the concepts and theories they learn. Another thing that reinforces the existence of local history material in the class X History textbook of the Merdeka curriculum is the alignment between learning outcomes, learning objectives and content in textbooks published by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia in 2021.